American Undergraduate Students’ Experiences in Conversational Partnerships with Chinese International Students - Sato, Takahiro; Miller, Ryan (Journal of International Students, 2021)
The purpose of the current study was to describe American domestic students’ experiences interacting with international students in a conversation partner program at an American university. This study used in-depth, semi-structured interviews grounded in positioning theory. Seven American students (three men and four women) participated. They served as conversation partners of Chinese international exchange students every fall semester. Four major interrelated themes emerged from the data. They were (a) seeking strategies for overcoming intercultural communication challenges, (b) addressing challenges for explaining sarcasm concepts, (c) finding mutual hobbies and interests, and (d) integrating field trips into the conversational program. This study encourages academic departments and faculty to develop a study group of conversational partnerships associated with value, origins, languages, and cultures of international students. This will contribute to a greater appreciation of the richness of diversity and to meaningful academic and social experiences at American universities for all students.